Interventions to improve primary healthcare in rural settings: A scoping review. - Kris Aubrey-Basler; Krystal Bursey; Andrea Pike; Carla Penney; Bradley Furlong; Mark Howells; Harith Al-Obaid; James Rourke; Shabnam Asghari; Amanda Hall (PLoS ONE)
Background Residents of rural areas have poorer health status, less healthy behaviours and higher mortality than urban dwellers, issues which are commonly addressed in primary care. Strengthening primary care may be an important tool to improve the health status of rural populations. Objective Synthesize and categorize studies that examine interventions to improve rural primary care. Eligibility criteria Experimental or observational studies published between January 1, 1996 and December 2022 that include an historical or concurrent control comparison. Sources of evidence Pubmed, CINAHL, Cochrane Library, Embase. Charting methods We extracted and charted data by broad category (quality, access and efficiency), study design, country of origin, publication year, aim, health condition and type of intervention studied. We assigned multiple categories to a study where relevant. Results 372 papers met our inclusion criteria, divided among quality (82%), access (20%) and efficiency (13%) categories. A majority of papers were completed in the USA (40%), Australia (15%), China (7%) or Canada (6%). 35 (9%) papers came from countries in Africa. The most common study design was an uncontrolled before-and-after comparison (32%) and only 24% of studies used randomized designs. The number of publications each year has increased markedly over the study period from 1-2/year in 1997-99 to a peak of 49 papers in 2017. Conclusions Despite substantial inequity in health outcomes associated with rural living, very little attention is paid to rural primary care in the scientific literature. Very few studies of rural primary care use randomized designs.